The Effectiveness of Financial Technology and Financial Literacy on Financial Analysis for Small and Medium Enterprises - Nusa, Inta Budi Setya; Rahmawati, Juwita Sri (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purposes of this study are 1) To test and analyze the effect of Financial Literacy on Financial Technology 2) To test and analyze the effect of Financial Literacy on  financial  analysis  for small and medium enterprises, 3) To test and analyze how much influence Financial Literacy has on  financial  analysis  for small and medium enterprises. This study uses a quantitative approach with philosophical considerations of positivism, including applied research, and including descriptive research. The research design used is correlational research, namely testing and estimating the relationship of many variables both partially and simultaneously using multiple regression methods from data harvesting research. This research uses panel data regression analysis with (1) Common Effect with the most basic model or estimation method in regression panel data, which still uses the ordinary least squares (OLS) principle, (2) Fixed Effect uses the dummy variable technique, (3) Random Effect Model (REM) or Generalized Least Square techniques. The research data uses a quantitative sampling method with random sampling systematically using intervals in selecting research samples obtained from data that can be measured by statistical techniques, with a total sample of 179 small and medium enterprises in Bandung. The results of the study show that (1) Financial Literacy can increase the knowledge of small and medium enterprises on the use of Financial Technology (2) there is an effect of Financial Literacy on  financial analysis   in small and medium enterprises. Financial literacy has a positive influence on individual welfare because of its very strong influence on financial conditions. By increasing the knowledge, confidence, and skills a person or the wider community can manage their finances well, their economic welfare tends to be better.